Analysis of the Effectiveness of Pregnancy Exercise in Reducing Pregnancy Complaints - Anindita, Hanifah; Aurelia, Renata (International Journal of Nursing and Midwifery Research, 2024)
This study investigates the effectiveness of prenatal exercise in reducing various pregnancy complaints among expectant mothers. A sample of 300 pregnant women was randomly assigned to an exercise intervention group or a control group receiving standard prenatal care. The results indicated that regular physical activity significantly alleviated musculoskeletal pain, improved mental health, and reduced the incidence of gestational diabetes and preeclampsia. Additionally, participants in the exercise group experienced shorter labor durations and lower cesarean section rates, alongside enhanced sleep quality and effective weight management. These findings underscore the importance of integrating structured exercise programs into prenatal care guidelines. The study highlights the need for healthcare providers to promote physical activity as a critical component of maternal health, ultimately contributing to better health outcomes for both mothers and their babies.